1994
DOI: 10.1128/jb.176.24.7468-7475.1994
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence that the gacA gene encodes the cognate response regulator for the lemA sensor in Pseudomonas syringae

Abstract: Mutational analysis of the bean-pathogenic Pseudomonas syringae pv. syringae strain B728a has led to the genetic identification of the gacA gene as encoding the response regulator for the unlinked lemA sensor kinase. The analysis of a collection of spontaneous mutants of P. syringae pv. syringae suggested that the gacA gene was involved in lesion formation and the production of protease and syringomycin. The gacA gene originally was identified as a regulator of extracellular antibiotic production by Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
128
1
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 37 publications
3
128
1
3
Order By: Relevance
“…2). Furthermore, the GacA proteins of P. syringae (Rich et al, 1994) and P. viridiflava (Liao et al, 1996) showed 99% identity with each other and 89% identity with GacA of P. aeruginosa (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Furthermore, the GacA proteins of P. syringae (Rich et al, 1994) and P. viridiflava (Liao et al, 1996) showed 99% identity with each other and 89% identity with GacA of P. aeruginosa (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…GacA is part of a two-component system and belongs to the FixJ family of response regulators (Laville et al, 1992). The cognate sensor appears to be the transmembrane protein LemA (Hrabak and Willis, 1992;Rich et al, 1994). Both the gacA and lemA genes are highly conserved in fluorescent pseudomonads (Liao et al, 1994;Corbell and Loper, 1995;Grewal et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response-regulator GacA and the corresponding sensor LemA are components of a highly conserved signal pathway within the genus Pseudomonas (Gaffney et al, 1994;Rich et al, 1994;Corbell & Loper, 1995;Haas & Carruthers, 1996, Université de Lausanne, Switzerland, personal communication). GacA is a response regulator in the Fix-DegU family of two-component regulatory systems Gaffney et al, 1994) and a conserved regulator of virulence factors in Pseudomonas aeruginosa (Rahme et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors that influence the expression of these small RNAs, the DNA-binding protein GacA stands out as a major activator (19,20). The response regulator GacA is activated by phosphorylation from the cognate membrane-bond sensor GacS (21)(22)(23)(24).…”
mentioning
confidence: 99%